Kontribusi al-QirÃ¢âÃ¢t al-TafsÃ®rÃ®yah dalam Penafsiran al-Qurâan - Nur, Afrizal (MUTAWATIR, 2011)
QirÃ¢âat urgency in order to understand the Koran was not able to be underestimated, and we must not regard the issue as a matter of considerable qirÃ¢âat only borne by the smallest group. The Companions are characters who have a great contribution in the history of popularizing various versions qirÃ¢âÃ¢t including qirÃ¢âÃ¢t tafsÃ®rÃ®yah, their participation in the development of the understanding of the verses of the Koran are very large. QirÃ¢âat is one pillar of the pillars of the source of interpretation by other sacred texts (al-maâthÃ»r). Based on the explanation, then we know that qirÃ¢âÃ¢t tafsÃ®rÃ®yah definitely has a share and a huge contribution in the interpretation and to produce law, so therefore it becomes very urgen to study it comprehensively in order to practice the Quran to practice perfect.